Correction: Bifunctional scaffolds for the photothermal therapy of breast tumor cells and adipose tissue regeneration. Issue 21 (9th May 2019) - Wang, Xiuhui; Zhang, Jing; Li, Jingchao; Chen, Ying; Chen, Yazhou; Kawazoe, Naoki; Chen, Guoping
Abstract : Correction for 'Bifunctional scaffolds for the photothermal therapy of breast tumor cells and adipose tissue regeneration' by Guoping Chen et al., J. Mater. Chem. B, 2018, 6, 7728–7736.